The impacts of health insurance on financial strain for people with chronic diseases - Zixuan Peng; Li Zhu (BMC, 2021)
Abstract Background Due to ongoing expenses for both short-term and long-term needs for health services, people with chronic diseases tend to struggle with financial hardship. Health insurance is employed as a useful tool in aiding people to solve such financial strain. This study aims to examine and compare the impacts of public and private health insurance on solving financial barriers for people with chronic diseases. Methods This research obtained an outpatient sample consisted of 1739 individuals and an inpatient sample consisted of 1034 individuals. We employed a Chi-square test and a two-sample T-test to explore differences in financial strain and insurance status between people with chronic diseases and those without. Then we adopted binary logistic regression technique to assess the impacts of different types of health insurance on outpatient and inpatient financial strain for people with chronic diseases. Results Our research has five key findings: first, people with chronic diseases were more likely to experience both the outpatient and inpatient financial strain (P < 0.01); second, public health insurance was found to reduce the outpatient financial strain; third, private health insurance was found to positively associate with inpatient financial barriers; fourth, Urban Employment Insurance (UEI) was expected to reduce both the outpatient and inpatient financial barriers, while self-paid private insurance (SPI) was positively associated with inpatient financial barriers; and fifth, income was identified as a positive predictor of having outpatient and inpatient financial strain. Conclusions Public health insurance has the potential to reduce the outpatient financial strain for people with chronic diseases. Private health insurance was identified as a positive predictor of inpatient financial strain for people with chronic diseases. Policy should be proposed to promote the capacity of public health insurance and explore the potential effects of private health insurance on solving the inpatient financial barriers faced by people with chronic diseases in China.